Identification of Circular RNA Expression Profiles in White Adipocytes and Their Roles in Adipogenesis - Zhang, Peng-peng; Han, Qiu; Sheng, Ming-xuan; Du, Chun-yu; Wang, Ya-ling; Cheng, Xiao-fang; Xu, Hai-xia; Li, Cen-cen; Xu, Yong-jie (Frontiers in Physiology, 2021)
Obesity and its related metabolic diseases have become great public health threats worldwide. Although accumulated evidence suggests that circRNA is a new type of non-coding RNAs regulating various physiological and pathological processes, little attention has been paid to the expression profiles and functions of circRNAs in white adipose tissue. In this study, 3,771 circRNAs were detected in three stages of white adipogenesis (preadipocyte, differentiating preadipocyte, and mature adipocyte) by RNA-seq. Experimental validation suggested that the RNA-seq results are highly reliable. We found that nearly 10% of genes which expressed linear RNAs in adipocytes could also generate circRNAs. In addition, 40% of them produced multiple circRNA isoforms. We performed correlation analysis and found that a great deal of circRNAs (nearly 50%) and their parental genes were highly correlated in expression levels. A total of 41 differential expression circRNAs (DECs) were detected during adipogenesis and an extremely high ratio of them (80%) were correlated with their parental genes, indicating these circRNAs may potentially play roles in regulating the expression of their parental genes. KEGG enrichment and GO annotation of the parental genes suggesting that the DECs may participate in several adipogenesis-related pathways. Following rigorous selection, we found that many up-regulated circRNAs contain multiple miRNAs binding sites, such as miR17, miR-30c, and miR-130, indicating they may potentially facilitate their regulatory functions by acting as miRNA sponges. These results suggest that plenty of circRNAs are expressed in white adipogenesis and the DECs may serve as new candidates for future adipogenesis regulation.